2017
DOI: 10.1097/qad.0000000000001511
|View full text |Cite
|
Sign up to set email alerts
|

Impact of comorbidity and ageing on health-related quality of life in HIV-positive and HIV-negative individuals

Abstract: In a cohort of largely well suppressed HIV-positive participants and HIV-negative controls, HIV-positive status was significantly and independently associated with worse physical and mental HRQL and with an increased likelihood of depression. Our finding that a higher number of comorbidities was independently associated with worse physical HRQL reinforces the importance to optimize prevention and management of comorbidities as the HIV-infected population continues to age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
58
1
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 71 publications
(69 citation statements)
references
References 33 publications
6
58
1
1
Order By: Relevance
“…A summary count of physical comorbidities was calculated. Mental illness was excluded from the count of comorbidities and evaluated as a single dichotomous variable, because HIV may impact mental health and mental health may worsen HRQOL through different mechanisms than physical comorbidities . Two survey items, “What is your race?” and “are you Spanish/Hispanic/Latino?” were collapsed and dichotomized as white/non‐Hispanic versus all other identities.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A summary count of physical comorbidities was calculated. Mental illness was excluded from the count of comorbidities and evaluated as a single dichotomous variable, because HIV may impact mental health and mental health may worsen HRQOL through different mechanisms than physical comorbidities . Two survey items, “What is your race?” and “are you Spanish/Hispanic/Latino?” were collapsed and dichotomized as white/non‐Hispanic versus all other identities.…”
Section: Methodsmentioning
confidence: 99%
“…GBM living with HIV also experience less social support, a greater risk of social isolation, and higher distress resulting from HIV‐related stigma compared with non‐GBM living with HIV . Previous studies have found that people living with HIV have worse physical and mental HRQOL and an increased likelihood of depression than HIV‐negative individuals . In addition, the combination of HIV infection and comorbid conditions may result in even poorer HRQOL …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering a longer life expectancy, the care and treatment of PLWHA should focus not only on continued medical treatment improvements but also on the individual’s quality of life. Prior research shows that PLWHA report lower health-related quality of life (QOL) and a higher prevalence of depression relative to the general population (13) and individuals uninfected with HIV (12). Furthermore, QOL is associated with poor clinical outcomes such that individuals who report lower QOL also have lower CD4 counts (14).…”
Section: Introductionmentioning
confidence: 99%
“…The presence -of neuropsychiatry co-morbidity in the pathophysiology of HIV compounds the suffering and detrimental prognosis of those afflicted with a complex relationship between HIV infection and psychiatric co-morbidity [4,5]. For example, HIV-positive status was significantly and independently associated with worse physical and mental health-related qualityof life and with an increased likelihood of depression [6]. Heroin administration, with or without smoking and cannabis, has emerged as a significantly destructive dimension of the HIV epidemic in Kenya [7].…”
Section: Editorialmentioning
confidence: 99%